2014
DOI: 10.1186/1471-2474-15-273
|View full text |Cite
|
Sign up to set email alerts
|

The shift of segmental contribution ratio in patients with herniated disc during cervical lateral bending

Abstract: BackgroundAbnormal intervertebral movements of spine have been reported to be associated with trauma and pathological conditions. The importance of objective spinal motion imaging assessment in the frontal plane was frequently underestimated. The clinical evaluation of the segmental motion contribution could be useful for detecting the motion pattern of individual vertebrae. Therefore the purpose of this study was to investigate the shift of segmental contribution ratio in patients with herniated disc during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The MATLAB computer programs were written to construct the midplanes of the vertebrae defined as a line running through the midpoints between the anterior and posterior two corners, and the bisectrix between the two midplanes were derived [ 31 ]. The perpendiculars were constructed from the anterior–inferior corners of the cranial vertebra and anterior–superior corner of caudal vertebra onto the bisectrix.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MATLAB computer programs were written to construct the midplanes of the vertebrae defined as a line running through the midpoints between the anterior and posterior two corners, and the bisectrix between the two midplanes were derived [ 31 ]. The perpendiculars were constructed from the anterior–inferior corners of the cranial vertebra and anterior–superior corner of caudal vertebra onto the bisectrix.…”
Section: Methodsmentioning
confidence: 99%
“…To compensate for variations in stature and radiographic magnification, the mean depth of the caudally adjacent vertebra was used to normalize the measurements of intervertebral alignment relationships. The MATLAB computer programs were written to construct the midplanes of the vertebrae defined as a line running through the midpoints between the anterior and posterior two corners, and the bisectrix between the two midplanes were derived [31]. The perpendiculars were constructed from the anterior-inferior corners of the cranial vertebra and anterior-superior corner of caudal vertebra onto the bisectrix.…”
Section: Videofluoroscopic Image Measurement and Data Analysismentioning
confidence: 99%
“…In addition, some studies suggested that movement abnormalities induced by cervical spine disease, disk fusion or arthroplasty may be the result of the alteration of SCHMs, while constant SCHMs cannot describe these special circumstance. 42,43 As a consequence, dynamic SCHMs could better reflect inherent natural biomechanics at each disk level. However, the out-of-plane CM is mainly due to the oblique orientated facet joints.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, neck pain is often described by subjective signs and symptoms. However, objective measures of neck pain has been used in previous studies such as reduced range of motion, decreased cervical muscle strength, lower movement velocity, increased neck reposition error, altered cervical joint motion and altered pressure pain sensitivity (Bahat et al, 2010;Dvir and Prushansky, 2008;Johnston et al, 2008;Lan et al, 2014;Madrid et al, 2016;Sjolander et al, 2008;Tsang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Individual cervical joint motion has been reported to be more important compared with total range of motion (ROM) in diagnosis and decision of surgery and postoperative assessments (Branney and Breen, 2014;Lan et al, 2014;Schwab et al, 2006). Anatomy dictates a difference in deep and superficial cervical muscles ability to influence single joint motion, as only the deep muscles such as the multifidus can directly control the motion of a single joint .…”
Section: Introductionmentioning
confidence: 99%